Critical success factors on small ruminant farming - Yusoff, Melissa Alina (2016)
Small ruminants belong to the Family: Bovidae, Subfamily: Caprinidae, and Genus: Ovis and Capra. In general the word small ruminant refer to sheep (Ovis aries), goats (Capra aegagrus hircus), and their exotic relatives of the genus ovis and capra. In Malaysian economy, livestock industry plays a vital role in terms of value-added and employment. Small ruminants are the fourth major livestock after swine, chicken and cattle. The contribution of the small ruminant industry to the agriculture output growth is becoming more important and requires highly significance. Problems confronting the small ruminant farming in Malaysia include, feed price, breed and stock, price of meat and live small ruminant, ranchers’ skills, farm management and capital for rearing small ruminants. However, the local breed is less suitable for commercial or large-scale production. Lack of feed quality and feed processing technology in the local market to support the growth of import breeds. Although there is a suitable technology for breeding, the government is still not ready to adopt the technology at this time to improve the productivity of local breeds. The government is giving more emphasis on commercial agriculture with plantation crops such as rubber, oil palm and coconut, which has been proven to increase the national economy. The above mentioned problems and issues are the factors that may influence the success of farming in Malaysia. The general objective of this study was to identify the critical success factors of small ruminant farming among the selected small ruminant ranchers in Peninsular Malaysia. In addition, the specific objectives of this study were; to determine the respondent’ perception and perception level toward successful factors on small ruminant farming, to clarify the relationship between socio-economic characteristics and the respondents’ perception level towards successful factors on small ruminants farming, to identify the relationship between selected farm profile and successful factor on small ruminants farming and to examine which are the Critical Success Factors on small ruminant farming. Therefore, data for this study was collected through field work undertaken during 2013 to 2014 from the different states of Peninsular Malaysia such as Kelantan, Terengganu, Pahang, Johor, Negeri Sembilan, Melaka, Selangor, Perak, Kedah, Perlis and Pulau Pinang. The respondents were small ruminant ranchers and using a structured questionnaire as a research instrument. A total of six hundred (600) respondents were interviewed to obtain their perceptions towards success factors that influence on small ruminant farming. However, there were constraints in the process of survey to identify the respondents and obtain their positive cooperation. Ranchers were categorized according to the number of breed and stock that are owned by ranchers such as small-scale (below 50), medium-scale (51-100), large-scale (100-150) and extra large-scale (150 and above). From this study it was found that almost 84.7 % of ranchers were below 50 years and almost 67.7 % of respondents reared small ruminants as a part time occupation. The result from mean ranking analysis showed that the highest success factors were technical skills (4.255), followed by feed source (4.246), while the lowest factor was recognized as neighbourhood relations (2.353). The chisquare analysis has been done to examine the association between the socio-economy and the respondent’ perception level of factors that influence the success on small ruminant farming. From the study several critical success factors were identified which influenced the small ruminant farming in Malaysia trough the exploratory factor analysis. The results revealed that the critical success factors on small ruminant farming were labelled as family support, government support and policies, labour, production system, farm management, extension services, disease and prevention management, technical skill, farm operation, marketing tool and strategies, neighbourhood relationship, feeding strategies and feed sources. These finding emphasized the need for ranchers to consider the critical success factors related to success on small ruminant farming. The results also displayed an overview of the opportunities and potential of the small ruminant that can be referred by individuals who want to participate in this industry. In conclusion, this study has been given a better understanding and knowledge to the livestock extension agents, policy makers and researchers about the critical successes factors which are family support, government support and policies, labour, production system, farm management, extension services, disease and prevention management, technical skill, farm operation, marketing tool and strategies, neighbourhood relationship, feeding strategies and feed sources that have been found in this study to solve the problems and plan the strategies to increase self-sufficiency level of small ruminant industry in Malaysia.